Coexistence of three EGFR mutations in an NSCLC patient: A brief report. Issue 4 (November 2018) - Belardinilli, Francesca; Gradilone, Angela; Gelibter, Alain; Zani, Massimo; Occhipinti, Mario; Ferraro, Sergio; Nicolazzo, Chiara; Coppa, Anna; Giannini, Giuseppe
Background: The epidermal growth factor receptor (EGFR) represents a molecular target for tyrosine kinase inhibitors for non-small cell lung cancer (NSCLC) patients with a mutation in the EGFR gene. Mutations of the EGFR gene that occur at a single position in NSCLC tissue are found as single, whereas two or more mutations on the same allele are poorly detected and investigated. Patient and methods: We investigated the presence of the EGFR gene mutations in tumor tissue by Sanger sequencing and ion torrent sequencing in an NSCLC patient at Stage IV of disease. Results: We found the presence of three coexisting mutations on the EGFR gene—two of which on exon 21 are present on the same allele, and the third, on exon 20, was analyzed by Sanger sequencing of the peripheral blood lymphocytes. The patient staged as cT4N0M1c (Stage IV) and started afatinib 40 mg daily 8 months ago, showing a clinical benefit. Conclusion: In this report we describe the case of an NSCLC patient harboring three coexisting mutations on the EGFR gene, two of which are present on the same allele. This mutation pattern may represent, for patient progeny, a genetic risk of cancer development. Therefore it should be possible to obtain screening guidelines to improve the risk calculation for lung cancer susceptibility in the future.